Are moral intuitions intellectual perceptions? - Dario Cecchini (Rivista Internazionale di Filosofia e Psicologia, 2022)
This paper discusses an influential view of moral intuition, according to which moral intuition is a kind of intellectual perception. The core claim of this quasi-perceptualist theory is that intuitions are like perceptual experiences in presenting propositions as true. In this work, it is argued that quasi-perceptualism is explanatorily superfluous in the moral domain: there is no need to postulate a sui generis quasi-perceptual mental state to account for moral intuition since rival theories can explain the salient mental features of moral intuition. The essay is structured into three main sections. In a first one, I introduce the quasi-perceptualist view of moral intuition. In the second, I show that ordinary accounts can explain the salient psychological features of moral intuition without referring to intellectual perceptions. Finally, in the third section, I discuss whether moral intuitions have presentational phenomenology like perceptual experiences.